In search of excellence in life - Shaya'a Othman; Kolej Universiti Islam Antarabangsa Selangor (Shah Alam : Majlis Agama Islam Selangor, 2008)
Experiences from the well known persons which include scientists, scholars, intellectuals and priests from all over the world.
Keywords: Excellence; Excellence -- Religious aspects